Gender-specific lethality due to carbon monoxide poisoning in Morocco - Chahboune Mohammed (EDP Sciences, 2021)
The objective of this study is to assess trends in death cases caused by carbon monoxide poisoning and to determine the possible reasons for a risk predisposition for a given sex in the event of a possible trend. In doing so, professionals working in the field of prevention take into account in control programs. Methods: Study of the regional and national evolution of sex-specific lethalities due to carbon monoxide poisoning based on deaths reported by the Anti-poison Center and Pharmacovigilance (CAPM) in the 16 regions for the period 1999-2013. Results: The chronological evolution of case-specific mortality rates on the whole shows an increasing trend for both sexes, which is in perfect proportion with the growth of deaths reported because of CO in the different regions. However, the values for the male, whose average for the period studied is 1.106%, are larger than those for females, whose average is only 0.618%. This more masculine tendency of lethalities cannot obviously be attributed to sex, nor to the particularities of deadly human CO exposure since all deaths are accidental and not related to socio-professional characteristics. Conclusion: The fatal risk in case of CO intoxication seems to favor a rather masculine superiority. This difference in lethality is simply explained by differences in the frequencies of poisoning and their fatal evolutions. Indeed, the quotient would be more masculine since the deaths due to the CO are practically similar for both sexes, whereas the frequency of the intoxications is more feminine.